Formal synthesis of cochlearol A, a meroterpenoid with renoprotective activity. Issue 19 (7th May 2020) - Naruse, Kazumi; Katsuta, Ryo; Yajima, Arata; Nukada, Tomoo; Watanabe, Hidenori; Ishigami, Ken
Graphical abstract: Highlights: We succeeded in formal synthesis of cochlearol A, a renoprotective meroterpenoid. Characteristic skeleton was constructed by intramolecular acetal formation. Key spiroepoxide was prepared under Concellón's conditions. Abstract: Cochlearol A, a renoprotective meroterpenoid isolated from Ganoderma cochlear, was formally synthesized by intramolecular acetal formation. Its characteristic perhydro-3, 9a-epoxybenzo[ c ]oxepine skeleton was stereoselectively constructed by intramolecular acetal formation employing spiroepoxide as a key intermediate, which was prepared via benzylic oxidation under Nicolaou's conditions employing photochemically activated Pb(OAc)4 and introduction of epoxide under Concellón's conditions using diiodomethane and methyllithium.